“Located on Land in Nova Scotia”: British Soldier Settlement after the Napoleonic Wars - Miles, William R.; Vance, Michael E. (Acadiensis, 2023)
Demobilized British soldiers settled throughout the British Empire after the Napoleonic Wars, including Nova Scotia. In the aftermath of the War of 1812, a group of veterans were located along the Annapolis Road to provide a land route between Halifax and Annapolis Royal. Despite the overall failure of the settlement scheme, the veterans who remained on their land grants were able to do so because of regimental links, family and denominational ties, and state support through British Army pensions. In realizing imperial claims, these soldier settlers contributed to the disruption of Mi’kmaw communities in the interior of the colony.